-7p-(-7+5p)=-4(3p-7)

Simple and best practice solution for -7p-(-7+5p)=-4(3p-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7p-(-7+5p)=-4(3p-7) equation:


Simplifying
-7p + -1(-7 + 5p) = -4(3p + -7)
-7p + (-7 * -1 + 5p * -1) = -4(3p + -7)
-7p + (7 + -5p) = -4(3p + -7)

Reorder the terms:
7 + -7p + -5p = -4(3p + -7)

Combine like terms: -7p + -5p = -12p
7 + -12p = -4(3p + -7)

Reorder the terms:
7 + -12p = -4(-7 + 3p)
7 + -12p = (-7 * -4 + 3p * -4)
7 + -12p = (28 + -12p)

Add '12p' to each side of the equation.
7 + -12p + 12p = 28 + -12p + 12p

Combine like terms: -12p + 12p = 0
7 + 0 = 28 + -12p + 12p
7 = 28 + -12p + 12p

Combine like terms: -12p + 12p = 0
7 = 28 + 0
7 = 28

Solving
7 = 28

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5(1+7)-5=175 | | x+4/15=-1 | | (7x^2-7x+8)+(9x^3-5x)= | | 3(x+3)+12=6x+3 | | 5(2a-4b)= | | -4(n+6)=12 | | 19=4+3v | | -x-4+3x=x-3+1 | | 7(x+5)=13 | | 4-6a+4a=-115(7-2a) | | 5x+47= | | 11/6x6/35 | | 4(2a-6)+8b= | | (3x+39/8)=0 | | 7k-2(3k+1)= | | 5x-1+x=15 | | 11=((7w-9)/2)+((8w+1)/5) | | y/8+4=6 | | 9(2/3+x)=24 | | 4x+9=8-6x | | 18-.10x=34 | | 3[7r-7]=-6+6r | | 7n-5n=9(n+7)-7(n+10) | | -5x1/4x4 | | -2/8n=3 | | 5n-3=3n-55 | | m/2=-9 | | 6x-17=11x+10 | | 12y+4=9y-5 | | 59-(G/2)=54 | | -(10x-10)=5(6x-6) | | (x-4)(5x-2)-3(x-4)=0 |

Equations solver categories